Acibenzolar-S-metil no manejo integrado da ferrugem e cercosporiose do cafeeiro - Fernandes, Luiz Henrique Monteiro (2009)
The current work was aimed at evaluating the resistance inducer Acibenzolar-S-methyl (ASM) for the control of coffee rust and brown eye spot at field conditions. Its direct effect against Hemileia vastatrix was also assessed in vitro and by using scanning electron microscopy, SEM. In the field experiment carried out at the Cascavel Farm, Carmo da Cachoeira country, Minas Gerais, with the Mundo Novo cultivar during two years of evaluation, 2008 and 2009. ASM had different behavior, depending on evaluation year. Disease control with ASM was as effective as the systemic fungicide treatment, only during the low yield year, where disease incidence was not so high. On the in vitro test, ASM did not show direct toxic effect against urediniospores of H. vastatrix, different from the phosphytes and the fungicide treatment. SEM studies confirmed in vitro results, where ASM treatment did not interfere on the germination and development of the germinative tube of H. vastatrix urediniospores, inoculated on coffee leaves. The direct toxic effect against the pathogen was demonstrated when either manganese phosphyte or systemic fungicide was used.